Enabling Impacts: Building a Broader Impacts Community of Practice at a Land-Grant University - Miles McNall; Lauren Aerni-Flessner; Denice Blair; Sara Steenrod; Angie Kankula (The University of Alabama, 2024)
The Broader Impacts (BI) activities required of researchers funded by the National Science Foundation (NSF) often involve public engagement, including K-12 outreach, informal science education, public exhibits and performances, advocacy and policy change, and business and entrepreneurship. The ARIS Broader Impacts Toolkit (Advancing Research Impacts in Society, 2024) is an online resource designed to help researchers develop BI plans for their NSF proposals. Several elements of the Toolkit address critical aspects of public engagement, making the Toolkit a valuable resource for researchers new to BI or public engagement, especially when integrated into wider BI communities of practice. We discuss how the national-level BI Community of Practice (BI-CoP) developed and sustained by the NSF-funded Center for Advancing Research Impacts in Society (ARIS) contributed to the development and continuing evolution of an institutional-level BI CoP at a large land-grant public university. The personal narratives of members of the institutional-level BI-CoP reveal how the ARIS BI-CoP has supported their learning, fostered collaboration around BI at their institution, supported the development of an institutional BI-CoP, and increased their capacity to assist researchers with developing and implementing BI plans. The experiences of consultants and researchers demonstrate that supportive and well-resourced BI-CoPs at the national and institutional level are essential for making effective use of the Toolkit and developing BI plans that are innovative, inclusive, and impactful.